Analisis Pemeliharaan Sarana dan Prasarana Peralatan Air di Kantor Pencarian dan Pertolongan Palembang - Pudiyanto, S.; Sulastri, Sri; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2025)
Analysis of the maintenance of water equipment facilities and infrastructure at the Palembang SAR Office is an important effort in ensuring operational continuity and optimal availability of facilities. This study aims to evaluate the effectiveness of existing maintenance strategies and provide recommendations for improvement.The research method involves field surveys to identify the physical condition of water equipment, such as water pumps, storage tanks, and distribution lines. Data was also collected through interviews with technical and managerial staff to understand ongoing maintenance practices. The analysis results show that although maintenance efforts have been carried out, there are still several areas that need further attention. Factors such as lack of structured maintenance planning, lack of use of equipment condition monitoring technology, and lack of human and financial resources are the main obstacles.Recommendations are provided to increase maintenance effectiveness, including the development of a more detailed preventive maintenance schedule, the implementation of a sensor-based equipment condition monitoring system, and increased training and development of human resources. By implementing these recommendations, it is hoped that maintenance performance can be improved and ensure the availability of reliable water facilities at the Palembang SAR Office.